A Comparison of Principals' Perceptions of Desired and Actual Participation in the Building Level Budget Decision Process - Barbara Y. LaCost; Mailyn L. Grady (Educational Considerations, 1992)
The data suggest that principals desire greater involvement and decentralization of the budget process.